Those about him remained silent : the battle over W.E.B. Du Bois - Bass, Amy (University of Minnesota Press, 2009)
Amy Bass provides the first detailed account of the battle over W.E.B. Du Bois and his legacy, as well as a history of Du Bois's early life in Massachusetts. Showing the potency of prevailing, often hidden, biases, Those About Him Remained Silent is an unexpected history of how racism, patriotism, and global politics played out in a New England community divided on how--or even if--to honor the memory of its greatest citizen.